Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Spirituality of place and its relationship to job performance of public-school principals in Jerusalem governorate from their point of viewMrs. Lubna Mousa Abu Sarhan , Mr. Ayoub Mousa Olyan , Dr. Kamal Khalil Makhamra2. The reality of bullying against academically gifted students from the point of view of teachers in general education schools in the State of KuwaitCo-Prof. Salamah Ajaj ALenezi3. The reality of using the System of the management E-Learning Classera Among Al-Andalus private Schools in the City of Sakaka from the point view of the Teachers.Mrs. Arwa Abdullah Hulayyil Al-Ruwaili , Co-Prof. Saud Saad Fayez Al-Akloby4. Features of jihadist education in the verses of The Battle of Uhud in Surat Al-ImranMr. Abd Alhamid Hassan Nakouh5. The impact of the Omani values program on the moral intelligence of early education children in Sultanate of OmanDr. Mahfouda Rashid Said Al-Mushaiqri6. The effectiveness of Bulgarian bag exercises on some physical variables for students majoring in physical education (swimming course) Palestine Technical University – KadoorieDr. Bassam Hamdan Abdelrazeq , Mrs. Rawan Aref Ewedat7. Educational Guidelines Derived from Occasions of some Quranic Chapters: An Analytical StudyMr. Abdullah Fayez Dhaban Al- Dhaban
Keywords: Journal of Educational and Psychological Sciences